Natural Phaeosphaeride A Derivatives Overcome Drug Resistance of Tumor Cells and Modulate Signaling Pathways - Victoria Abzianidze; Natalia Moiseeva; Diana Suponina; Sofya Zakharenkova; Nadezhda Rogovskaya; Lidia Laletina; Alvin A. Holder; Denis Krivorotov; Alexander Bogachenkov; Alexander Garabadzhiu; Anton Ukolov; Vyacheslav Kosorukov (MDPI AG, 2022)
In the present study, natural phaeosphaeride A (PPA) derivatives are synthesized. Anti-tumor studies are carried out on the PC3, K562, HCT-116, THP-1, MCF-7, A549, NCI-H929, Jurkat, and RPMI8226 tumor cell lines, and on the human embryonic kidney (HEK293) cell line. All the compounds synthesized turned out to have better efficacy than PPA towards the tumor cell lines listed. Among them, three compounds exhibited an ability to overcome the drug resistance of tumor cells associated with the overexpression of the P-glycoprotein by modulating the work of this transporter. Luminex xMAP technology was used to assess the effect of five synthesized compounds on the activation of intracellular kinase cascades in A431 cells. MILLIPLEX MAP Multi-Pathway Magnetic Bead 9-Plex was used, which allowed for the simultaneous detection of the following nine phosphorylated protein markers of the main intracellular signaling pathways: a universal transcription factor that controls the expression of immune-response genes, apoptosis and cell cycle NFκB (pS536); cAMP-dependent transcription factor (CREB (pS133); mitogen-activated kinase p38 (pT180/pY182); stress-activated protein kinase JNK (pT183/pY185); ribosomal SK; transcription factors STAT3 (pS727) and STAT5A/B (pY694/699); protein kinase B (Akt) (pS473); and kinase regulated by extracellular signals ERK1/2 (pT185/pY187). The effect of various concentrations of PPA derivatives on the cell culture was studied using xCelligence RTCA equipment. The compounds were found to modulate JNK, ERK1/2, and p38 signaling pathways. The set of activated kinase cascades suggests that oxidative stress is the main probable mechanism of the toxic action of PPA derivatives.